The impact of fine particulate matter on depression: Evidence from social media in China - Yao Zhong; Jianxin Guo; Hongbiao Wang; Zhufeng Qiao; Jichun Zhao; Lei Chen; Ying Nie (PLoS ONE, 2025)
Depression is a significant public health issue in China that imposes a heavy economic burden on society and families. Using a dataset of 8.54 million Weibo posts from 284 prefecture-level cities across China between 2016 and 2019, we calculate the depression tendency index for residents in each city. Using the weighting of pollutants in nearby cities as an instrumental variable, we apply the two-stage least squares method to estimate the impact of PM2.5 on depression. The findings reveal that (1) air pollution markedly influences residents’ susceptibility to depression, and every 1 μg/m3 increase in the PM2.5 concentration results in a 0.0559% increase in the depression tendency value. (2) The influence of air pollution on residents’ depression exhibits a distinct weekly pattern, with individuals in heating cities, on weekdays, and in lower-income brackets being more impacted. (3) Our analysis of healthcare expenditures affirms that China’s environmental governance policies have yielded significant economic advantages. As mitigation strategies, we propose the adoption of air pollution evasion measures, persistent refinement and enforcement of air pollution regulatory policies to reduce environmental pollution-related damage, paying attention to groups at risk of depression and fostering a healthy society.